2019
DOI: 10.3390/ijms20112726
|View full text |Cite
|
Sign up to set email alerts
|

Cuscuta Species Identification Based on the Morphology of Reproductive Organs and Complete Chloroplast Genome Sequences

Abstract: The genus Cuscuta (Convolvulaceae) comprises well-known parasitic plants. Cuscuta species are scientifically valuable, as their life style causes extensive crop damage. Furthermore, dried seeds of C. chinensis are used as a Korean traditional herbal medicine. Despite the importance of Cuscuta species, it is difficult to distinguish these plants by the naked eye. Moreover, plastid sequence information available for Cuscuta species is limited. In this study, we distinguished between C. chinensis and C. japonica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Misuse of traditional medicines might result in severe harm to patients [87]. Thus, recent attempts have been made to improve the authentication of medicinal material using microscopic analysis [88][89][90]. Our studied character states revealed that the collected and purchased materials were identical and overlapping.…”
Section: Application For Authentication Of Herbal Medicinementioning
confidence: 86%
“…Misuse of traditional medicines might result in severe harm to patients [87]. Thus, recent attempts have been made to improve the authentication of medicinal material using microscopic analysis [88][89][90]. Our studied character states revealed that the collected and purchased materials were identical and overlapping.…”
Section: Application For Authentication Of Herbal Medicinementioning
confidence: 86%
“…sutchuenensis in Loranthaceae of Santalales [ 53 ], Epifagus virginiana in Orobanchaceae of Lamiales [ 54 ], Cuscuta chinensis and C . japonica in Convolvulaceae of Solanales [ 55 ]. Smaller chloroplast genomes were also found in some gymnosperms such as Welwitschia mirabilis in Welwitschiaceae of Welwitschiales [ 56 ], and Gnetum ula in Gnetaceae of Gnetales [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…These cp genomes have a conserved typically quadripartite structure, in which two inverted repeats (IRs) are separated by a large single‐copy region (LSC) and a small single‐copy region (SSC) (Palmer 1985, Wicke et al 2011). Due to its uniparental inheritance, conserved gene content and structure characteristics (Palmer 1985, Palmer et al 1988, Raubeson and Jansen 2005, Wicke et al 2011), the cp genome is valuable for studies on phylogeny, population genetics and species identification (Korpelainen 2004, Moore et al 2007, Ravi et al 2008, Liu et al 2019, Park et al 2019, Silva et al 2019, Asaf et al 2020, She et al 2020, Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%